(NwSEGDA W DU[E (B:s [(NPO\ZIQ(B] /s - (NaLQBXEW(B, (NwQ^ESLAW(B.s ((NkIEW (B:s (NkADRY(B,s, 2004)
(NcE PER[A ZB)QÆRKA WÆR[ÆW AWTORA(B. (Nw NIH JDETXSQ PRO DOBROTU Æ ^UJNÆSTX(B, (N[WIDKOPLINNÆSTX VITTQ Æ WÆRU W KRA]E MAJBUTNÃ(B, (NPOEZÆ@ SWÆTLIH PO^UTTÆW Æ NEPOWTORNÆSTX BUTTQ(B... (NrOZRAHOWANA NA [IROKE KOLO L@BITELÆW POEZÆÇ(B.s)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKAs)E -- (NpOEZ)QÆQs)E -- (NrOS)QÆJSXKOMOWNA(B.s)E